PENGEMBANGAN MODUL INTERAKTIF PADA PEMBELAJARAN GENETIKA UNTUK MENINGKATKAN HASIL BELAJARDAN PEMAHAMAN KONSEP SISWA SMA ISLAM BATU - Riyanto, Riyanto (JEMS Jurnal Edukasi Matematika dan Sains, 2015)
This study uses research and development (Research and Development / R & D) method. Model development of instructional media used is aDevelopment model consisting of ten steps, but in this study only compriseseight steps, namely: potential and problems, information gathering, productdesign, design validation, the revised design, product testing, product revision,and the final product. Based on the results of the validation interactive module Genetics bymatter experts and media experts shows that genetics interactive module isfeasible used with a percentage of the average score of 90%. Based on theresults of the validation interactive CD genetics by material experts showedthat the decent used by a score of 96% while the results validator of mediaexperts with regard to the feasibility of an interactive CD genetics show thatdecent used is by a score of 88% and an average rate of eligibility InteractiveCD showed that the decent genetics used is 92%, this indicates that theinteractive CD genetics can be applied in small scale to see the effectiveness ofthe implementation of this genetic interactive CD. Based on the results of a small-scale trial Genetics interactive moduleeffectively used by students seen from the kognitive learning outcomes reached85.3% and students understanding of concepts of 87.2%.Based on the researchresults, it can be concluded that genetics developed interactive module getsadequate assessment of experts, as well as the effective use of learning bystudents of class XII, SMA Islam Batu with kognitive learning outcomesreached 85.3% and students understanding of concepts of 87.2%.Keywords : geneticâs learning, interactive modul, Research and Developmentmethod.